2012
DOI: 10.1371/journal.pone.0043532
|View full text |Cite
|
Sign up to set email alerts
|

ARF6-Dependent Regulation of P2Y Receptor Traffic and Function in Human Platelets

Abstract: Adenosine diphosphate (ADP) is a critical regulator of platelet activation, mediating its actions through two G protein-coupled receptors, the P2Y1 and P2Y12 purinoceptors. Recently, we demonstrated that P2Y1 and P2Y12 purinoceptor activities are rapidly and reversibly modulated in human platelets, revealing that the underlying mechanism requires receptor internalization and subsequent trafficking as an essential part of this process. In this study we investigated the role of the small GTP-binding protein ADP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Genetic ablation of Arf6 in platelets enhanced clot retraction and spreading, indicating that endocytosis contributes to rapid platelet functions. These findings are consistent with Kanamarlapudi and colleagues who showed that Arf6 regulates P2Y trafficking in platelets as well as dynamin-dependent fission of coated vesicles during endocytosis[50]. Additionally, two Rab proteins (Rab4 and Rab11) are also involved in integrin-mediated fibrinogen uptake and trafficking in platelets[49, 51].…”
Section: Granular Secretion Mechanisms In Plateletssupporting
confidence: 87%
“…Genetic ablation of Arf6 in platelets enhanced clot retraction and spreading, indicating that endocytosis contributes to rapid platelet functions. These findings are consistent with Kanamarlapudi and colleagues who showed that Arf6 regulates P2Y trafficking in platelets as well as dynamin-dependent fission of coated vesicles during endocytosis[50]. Additionally, two Rab proteins (Rab4 and Rab11) are also involved in integrin-mediated fibrinogen uptake and trafficking in platelets[49, 51].…”
Section: Granular Secretion Mechanisms In Plateletssupporting
confidence: 87%
“…12 Arf6 also appears to play a role in the endocytosis and resensitization of P2Y receptors. 14 Taken together, these data suggest that Arf6 controls endocytic trafficking in a manner that may be responsive to both initial platelet activation and subsequent signaling from contactmediated pathways. The goal of this study was to further understand the action of Arf6 in platelets.…”
Section: Introductionmentioning
confidence: 73%
“…In another paper, it was claimed that both P2Y 1 -and P2Y 12 -mediated platelet responses desensitise rapidly, but by different kinase-dependent mechanisms [247]. The desensitization of the P2Y receptor on platelets requires receptor internalization, and it was claimed that the GTP-binding protein ADP ribosylation factor 6 is required for P2Y receptor internalization [248].…”
Section: Pathologymentioning
confidence: 99%